Pemanfaatan Google Analytics Sebagai Upaya Optimasi UX Untuk Meningkatkan Konversi Pada Website - Saraswati, I Gusti Agung Istri Bianca Githa; Putra, I Gusti Ngurah Anom Cahyadi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 3 (2024): JELIKU Volume 12 No 3, February 2024, 2024)
In a world driven by advances in technology, society uses technology more than ever to help support them in many ways. A few of the common ones are to have a business with information systems offline to help achieve their business goals and to have a website so that their business would have a presence online and can be reached globally by the international audience. With every aspect of modern technology, be it offline or online, the user interface and user experience plays a critical role in how the new technology can be usable and adaptable by users of the businesses, and their customers. In the online space, the user experience should be perfected in order to make the website more valuable, accessible, usable, desirable, trustable , and credible to help the user feel more comfortable using the website. This journal will cover how Google analytics can be used to optimize the user experience (UX) t o increase the conversion of a website. In order to analyze & enhance the UI and UX of a website, one needs to use both a heuristic approach or known as the rule of thumb approach coupled with a data analysis/ data-driven approach.  For the data analysis approach to work we would need to sample user traffic data of the website, and identify behavior trends, findings and make conclusions. There are many ways to attract user traffic to a website. Email channel, direct, organic social, organic search, and paid search and paid social are just a few of those many ways. The fastest way out of these options would be to attack traffic via ads placements or paid search ads and paid social ads which can used as a source of the traffic for the data analyses to function. that will be covered in this study. Once traffic is available, Google Analytics can be used to analyze traffic in order to improve the user experience of the website.  This journal has proven that google analytics can help the business to optimize the UX of our website. The goal of this business is to get the user to click the WhatsApp button and communicate with the owner. We get 11 users that click the WhatsApp button in January which is before the website UX is upgraded, 16 users in February when the new version design is launch, and the new one in March which has 25 users to click the WhatsApp button on website. This have been proven that the conversion rate of user clicking WhatsApp button is after the UX design have been launch is higher than before the website used the UX design.